Neural network in handwritten recognition system: A survey - Wan Ishak, Wan Hussain; Abdul Rahman, Shuzlina (2003)
Neural network is a branch of Artificial Intelligence that imitates the biological processing function of the brain. Neural network has been implemented in various applications. One of the applications is handwritten recognition system. Handwritten is the art of an individual, which is controlled by the function of the brain. Every individual has his or her own style of writing. Hence, reading the handwriting is sonmetimes quite difficult. Many researches have been done in this area and yet still continuing. This paper presents a survey on the application of neural networks in handwritten recognition system. Several methodologies including feature extractions, neural network models and algorithms are highlighted.